"Auditoría operativa y su incidencia en el departamento de colecturía de la unidad educativa adventista loma linda, cantón santa cruz, provincia de galápagos, período académico 2014-2015" - Hainán Zamora, Javier Oswaldo (2016)
The operational audit conducted on the Accounts Receivable Department of the Loma Linda School was made in order to understand the processes that take place within this department and to know any inconvenience in order to improve the service and moreover that provisions are met effectively and efficiently and that resources are used wisely. The methodology included the deductive and documentary method and observation techniques, surveys, data analysis provided by the institution, calculations, by which final results were obtained. Regarding the interview to assess internal control, COSO II method was used, which has eight components. In addition to this, staff surveys and interviews with managers, which were the most, used techniques as it is the most direct method to obtain concise information. As a result the methods used to collect pensions which fulfill their function but they must be applied with discipline because they are not often used as they should. As for the evaluation of the internal control of the Accounts Receivable Department, it was concluded that the confidence level was 85.87% and control risk was 14.13%, an acceptable figure, however, some aspects need improvement such as elaborating internal rules for collection, detailed review reports of monthly income, and little control in the application of methods to collect pensions or overdue payments. Likewise, it was accurately determined the non-performing loans of past years, and the annual employee turnover, which showed that five employees leave the company every year, which in turn implies that the administration work with employees should improve